Pengaruh Kompetensi Pedagogik Guru Pendidikan Agama Kristen (PAK) terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 2 Sipoholon Tahun Pembelajaran 2023/2024 - Leni Elisa Silaban; Risden Anakampun; Robinhot Sihombing; Damayanti Nababan; Raikhapoor Raikhapoor (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The research aims to determine the positive and significant influence of the pedagogical competence of Christian Religious Education teachers on the learning interest of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence on the pedagogical competence of Christian Religious Education teachers on the learning interest of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year. Quantitative descriptive research method with inferential statistical data analysis. The population of all class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year who are Protestant Christians is 108 people. The sample was random (random sampling) namely 50% of the total population, namely 54 people. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value rcount=0.684>rtabel=0.226 and tcount=6.762>ttable=2.00665 shows that there is a positive and significant relationship between the pedagogical competence of Christian Religious Education teachers and students' interest in learning. b) Regression equation. c) The determination test revealed that the magnitude of the effect was 46.79%. d) Hypothesis testing obtained Fcount=45.306>Ftable=3.15 then H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the pedagogical competence of Christian Religious Education teachers on the learning interest of class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year.